2008
DOI: 10.1158/1078-0432.ccr-07-5243
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Reproducibility of 3′-Deoxy-3′-[18F]Fluorothymidine Positron Emission Tomography Imaging in Patients with Non–Small Cell Lung Cancer

Abstract: Purpose Imaging tumor proliferation with 3′-deoxy-3′-[18F]fluorothymidine (FLT) and positron emission tomography is being developed with the goal of monitoring antineoplastic therapy. This study assessed the methods to measure FLT retention in patients with non-small cell lung cancer (NSCLC) to measure the reproducibility of this approach. Experimental Design Nine patients with NSCLC who were untreated or had progressed after previous therapy were imaged twice using FLT and positron emission tomography withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 12 publications
6
29
0
1
Order By: Relevance
“…Kenny et al (4) reported a DSD of 10.5% for SUV mean in breast cancer (n 5 8), which corresponds to an RC of 20.6%. Shields et al (34) used a repeatability metric that is not directly comparable to RC. However, they measured relative differences in SUV mean of up to 21% (non-small cell lung cancer, n 5 9).…”
Section: Discussionmentioning
confidence: 99%
“…Kenny et al (4) reported a DSD of 10.5% for SUV mean in breast cancer (n 5 8), which corresponds to an RC of 20.6%. Shields et al (34) used a repeatability metric that is not directly comparable to RC. However, they measured relative differences in SUV mean of up to 21% (non-small cell lung cancer, n 5 9).…”
Section: Discussionmentioning
confidence: 99%
“…Initial patient studies have further emphasized the potential of 18 F-FLT PET for monitoring tumor response to therapy. 18 F-FLT uptake in untreated tumors has been shown to be stable over time, with a test-retest reproducibility of less than 10% for standardized uptake values when patients were imaged twice within a week (17,18). In 19 patients with recurrent malignant brain tumors treated with irinotecan and bevacizumab, tumor response on 18 F-FLT PET after 1-2 wk of therapy correlated with overall survival at a high level of statistical significance.…”
Section: Imaging Of Tumor Cell Proliferationmentioning
confidence: 99%
“…Accumulation of FLT in proliferating cells reflects increased activity of both nucleoside transporters and thymidine kinase, which traps the tracer by phosphorylation. While FLT is not incorporated into DNA, the cellular uptake of FLT has been shown to correlate with proliferation [31]. The impact of antitumor treatment on FLT uptake is complex and not yet fully understood [32,33].…”
Section: Cell Proliferation/dna Synthesismentioning
confidence: 99%